ASSESSMENT OF WARSAW UNIVERSITY OF LIFE SCIENCES – SGGW STUDENTS’ BEHAVIOURS UNDER RISK - Podstawka, Marian; Gołasa, Piotr (Acta Scientiarum Polonorum. Oeconomia, 2019)
In this study, the authors made an attempt to verify the certainty effect and the rebound effect articulated in the 1970s by D. Kahneman and A. Tversky. The research was carried out on a sample of 500 students of economic and technical specializations at Warsaw University of Life Sciences. The authors formulated research hypotheses on how field of studies or gender influence decisions taken under risk. The outcomes were considerably similar to the results of D. Kahneman’s and A. Tversky’s research, which confirmed that the certainty effect and the rebound effect existed. One disapproved the hypothesis on gender influence and confirmed the hypothesis on the influence of the field of studies on taking decisions under risk. It was found that raising the amount of potential loss has an impact on the willingness to take risk so that the loss can be avoided.